Perancangan Sistem Informasi Berbasis Client-Server Pada Bagian Perencanaan Produksi dan Pengendalian Bahan Baku: Sebuah Studi Kasus - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT This paper aims to present a case study of the development of a client-server based information system on an industrial engineering application. For the purpose of confidentiality